Impediments to agricultural growth in Zambia - Wichern, Raier; Hausner, Ulrich; Chiwele, Dennis K. (International Food Policy Research Institute, 1999)
This paper has been prepared as part of the Zambia country study of the Macroeconomic and Regional Integration in Southern Africa (MERRISA) project and serves as a background paper for modeling exercises. The paper focuses on analyzing institutional constraints on the development of the agricultural sector in Zambia. It argues that by changing some of the rules and neglecting to integrate these changes into the complete institutional setting, policymakers have been unable to achieve their goals. Other constraints on Zambia's agricultural development are of a more technical nature. There are problems with Zambia's infrastructure. This paper argues that these are problems of the provision of public and merit goods mainly occurring in rural areas. Farmers emphasize their limited access to resources like credit, fertilizer, and draft animals. Although these problems could indicate market failures, it is the view of the authors that they are mainly due to transition uncertainties.